Development of Student Worksheets Based on Critical Thinking Skills at MAN 1 Medan - Elly Damayanti Pulungan, Sulastri, Mayang Mustika Sari, Wahyuddin Nur Nasution, Nirwana Anas (Education Achievement: Journal of Science and Research, 2023)
This study aims to develop Student Worksheets (LKPD) based on critical thinking skills. The development of LKPD was carried out using the 4D model, with a research design in the form of a one-group pre-test post-test design. The research activities were implemented in two replications during fiqh learning in grade XI IPS at MAN 1 Medan. The results of the study indicate that the LKPD meets the criteria for validity and effectiveness. The reliability and validity levels of LKPD each showed an average percentage of 86.35% and 92.64%. High n-gain values for critical thinking skills were demonstrated by the inference and strategy indicators. The legibility of LKPD was measured using a cloze procedure, which indicated a percentage of 95.38%. Student activities in this research were predominantly focused on completing LKPD. Based on the research findings, it can be concluded that the developed LKPD is suitable for improving critical thinking skills.